Utilização de resíduo de cama de frango na fertilização em cobertura de milho variedade em sistema agroflorestal - Oliveira, Duane Nascimento (Universidade Federal de São Carlos, 2020)
Corn is one of the most important crops in Brazil and in the world with a wide geographical area. Corn cultivation in Brazil is commonly performed by hybrid and transgenic materials. Forgotten, maize varieties are less and less used, and their social and genetic importance almost abandoned. The environmental and food concern has been gaining prominence in Brazil and in the world, alternative cultivation activities with agroecological and organic models are of paramount importance and supply the social, environmental and market necessity for products with practices with this cultivation profile, being a disclosure of alternative technical-scientific methodology to conventional means. The nutritional factor on maize production is of paramount importance for plant development, so alternative means to mineral and chemical fertilization using sources from organic matter may be an alternative means of production. There is a need for studies on fertilization with organic, efficient, sustainable and environmentally sound sources, as they avoid methods of major environmental impacts on corn crop, besides the lack of studies in the literature. In this context, an experiment was carried out, using organic source fertilization through poultry litter, in substitution of the cover mineral fertilizers, on green variety CATI 02, evaluating the productive performance of corn under the influence of treatments. In the experiment, topdressing fertilization with five different levels was used, relating to yields. n the experiment, topdressing fertilization with five different levels was used, relating to yields. The experiment was carried out at the Lagoa do Sino campus of the Federal University of São Carlos - UFSCar, Buri - SP, in the Agroforestry System (AS) area, in two seasons. The results obtained were promising and show the importance of alternative methodologies to conventional agriculture, which can work together or in substitution, aiming at a sustainable agriculture that brings income to farmers. The dissertation consists of the literature review, followed by the research works. Keywords: Agroecology, Zea mays, organic fertilization, Agroforestry systems.
Use of poultry litter waste in fertilization in corn cover variety in agroforestry system.
Keywords: Agroecologia; Zea mays; Adubação orgânica; Sistemas Agroflorestais; Agroecology; Organic fertilization; Agroforestry systems; CIENCIAS AGRARIAS::AGRONOMIA::FITOTECNIA; CIENCIAS AGRARIAS::AGRONOMIA; CIENCIAS BIOLOGICAS::BOTANICA::FISIOLOGIA VEGETAL::NUTRICAO E CRESCIMENTO VEGETAL